The Effect of Different Restorative and Abutment Materials on Marginal and Internal Adaptation of Three-Unit Cantilever Implant-Supported Fixed Partial Dentures: An In Vitro Study - KAHRAMANOĞLU, ERKUT; ÖZKAN, YASEMİN (WILEY-BLACKWELL, 2013)
PurposePassive fit is generally assumed to be a significant prerequisite for long-term implant success. The aim of this study was to evaluate the precision fit of three-unit implant-supported fixed partial dentures with different restorative and abutment materials on two implant systems: the Straumann and Astra Tech. Materials and MethodsTwo mandibular epoxy resin models (one for each implant system) were fabricated, and two implants were inserted at the first and second molar region. Poly(vinyl siloxane) impression material was used to make the dental impression. For each implant system, fifteen models were fabricated, and each group was divided into three subgroups (group 1: titanium abutment with metal framework, group 2: titanium abutment with zirconium framework, group 3: zirconium abutment with zirconium framework). The replica technique was used to examine the marginal and internal gap values. For each restoration, 20 measurements were performed, totaling 1200 measurements for all groups. Data were evaluated statistically using ANOVA and LSD post hoc test (p < 0.05). ResultsThe highest values at internal adaptation measurements were found at the occlusal surface for all groups. When the mean values of the marginal measurements were assessed, the lowest measurements were found in group 3 (51.416m), and the highest values were found in group 1 (79.394m). There were statistically significant differences between subgroups for marginal measurements (p < 0.05). ConclusionsAs included in our study, marginal measurement values were found to be 46 to 87m. The marginal discrepancy of the tested materials could be considered clinically acceptable.
Keywords: Abutment; implant; implant-supported prosthesis; precision fit; restorative material; ALL-CERAMIC CROWNS; ONE-PIECE CASTINGS; DENTAL PROSTHESES; FIT; FRAMEWORKS; METAL; ACCURACY; ZIRCONIA; TITANIUM; COPINGS